Selected radical azoinitiators in the synthesis of solvent-borne acrylic pressure-sensitive adhesives - Pabin-Szafko, Barbara; Wisniewska, Ewa; Czech, Zbigniew (Publishing House of Lviv Polytechnic National University, 2009)
Functional azoinitiators: 2,2’-azobis(2-methyl- 4-hydroxybutyl propionate) (AIB-BD), 2,2’-azobis[2- methyl-?-hydroxy-tri(oxyethylene) propionate] [AIBTri(OE)] and 2,2’-azobis[2-methyl-?-hydroxyoligo( oxyethylene) propionate] [AIB-OOE(400)] were used in radical polymerization of 2-ethylhexyl acrylate, methyl acrylate and acrylic acid in organic solvent ethyl тacetate to prepare solvent-borne acrylic pressure-sensitive adhesives (PSA). After polymerization the viscosity, molecular weight and polydispersity of received acrylic PSA have been evaluated and compared with the product of polymerization initiated by the conventional azoinitiator 2,2’-azobisisobutyronitrile (AIBN). Показана можливість використання функційних азоініціаторів: 2,2’-азобіс(2-метил-4-гідроксибутил пропіонату), 2,2’-азобіс[2-метил-ω-гідрокси-три(оксиетилен) пропіонату] та 2,2’-азобіс[2-метил-ω-гідрокси-оліго(оксиетилен) пропіонату] в радикальній полімеризації 2-етилгексилакрилату, метилакрилату і метакрилової кислоти в органічному розчиннику етилацетаті для одержання обмежено розчинних акрилових клеїв, здатних склеюватись при надавлюванні.
Селективні радикальні азоініціатори у синтезі обмежено розчинних "пресованих" акрилових клеїв
Keywords: functional azoinitiators; acrylic monomers; radical polymerization; acrylic PSA; функційний азоініціатор; акрилові мономери; радикальна полімеризація; акрилові клеї